The Implementation of the Discovery Learning Model Using Higher Order Thinking Skills Booklet Media on Students' Critical Thinking Ability - Nurhikma Ramadhana; Nur Qamariah; Hanandita Veda Saphira (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2025)
Objectives: To implement and design learning models that incorporate appropriate instructional media, fostering critical thinking. Such an approach will facilitate the integration of three cognitive domains: knowing, applying, and reasoning. Methods: This study adopts a quasi-experimental design using a